The Effect of Implicitation & Explicitation Strategies on the Acceptance of Two Different Farsi Translations of George Orwell’s Animal Farm - Sepehri, Zhilla; Eslamieh, Razieh (International Journal of Linguistics, 2021)
Explicitating and implicitating are among the significant facets of texts in Translation Studies. They vary across languages in terms of the way and process of transferring into another language. This research presents a study of explicitation and implicitation in translation. Explicitating and implicitating shifts were manually identified in a corpus of English and their translations in presian. Explicitating and implicitating Shifts were classified according to Vahedi Kia’s (2011) framework. The study tries to explore the percentage of the usage of explicitations and implicitating in two different translations of George Orwell’s Animal Farm. The main aim of the study was to specify the relation and the Effect of implicitation & explicitation strategies on the acceptance of two different farsi translations of George Orwell’s Animal Farm. Unlike most other studies of explicitation in translation, the present study did not depart from the assumption of a ‘translation-inherent’, universal process of explicitation (cf. Blum-Kulka’s Explicitation Hypothesis). Rather, the prediction underlying the study was that every instance of explicitation (and implicitation) can be explained as a result of lexicogrammatical and/or pragmatic factors. This analysis has made it possible to compile a list of factors that regularly lead translators to explicitate or implicitate. The factors explain why implicitations are often outnumbered by the corresponding explicitations.